Diagnosis of training needs among AICLE teachers in initial training (European Journal of Child Development, Education and Psychopathology, 2021)
This research paper aims to uncover training needs of university students or pre-service CLIL teachers (N=19) through the process of presentation, explanation, and resolution of mathematical problems in English as a foreign language concerning four operations: addition, subtraction, multiplication, and division. The aim is to make sure whether the training needs are related to the pre-service CLIL teachers’ mathematical knowledge, language competence, or teaching skills. This is a descriptive correlational study with a quantitative approach, in which two research tools were used: A questionnaire answered before and after each mathematical problem by the students who performed as teachers, together with a voice recorder to collect their full discourses. Although the results do not reveal significant training needs, some weaknesses in terms of teaching skills are found. However, it is also worth considering the degree of difficulty of the mathematical problems focused on Primary Education Year 3. It would make it possible to infer probable complications in terms of content knowledge and language competence if the mathematical problems were designed for more advanced courses. Finally, the relationship between the results achieved and the objectives and research hypotheses is outlined.
Keywords: Teacher education; teaching practice; primary schools; bilingual education; English